TRADISI, IDENTITAS NASIONAL, DAN DINAMIKA BUDAYA DALAM NOVEL DUA IBU KARYA ARSWENDO ATMOWILOTO - Maharani, Pratiwi (Magistra Andalusia: Jurnal Ilmu Sastra, 2024)
This research investigates tradition, national identity, and cultural dynamics in Arswendo Atmowiloto's Dua Ibu using Stuart Hall's Cultural Studies approach. Qualitative research methods were used to analyze quotations describing aspects of culture and identity in the literary work. Substantial findings highlight the complexity of traditional values, generational value changes, and characters' internal conflicts that reflect cultural transformation in Javanese society. Stuart Hall's theory provides a strong framework for understanding how identity and culture are formed, maintained, and changed in the context of globalization. The relevance of these findings lies in the contribution to the understanding of the dynamics of Indonesian culture and national identity in the era of globalization. The implications of this research provide a basis for policy development that supports the preservation of culture and traditional values. Further research could involve comparative studies with other literary works or interdisciplinary approaches to explore the themes that emerge in this novel.